Social Panorama of Latin America and the Caribbean 2022 - Economic Commission for Latin America; the Caribbean (United Nations, 2023)
This publication presents the relevant macroeconomic background in terms of the evolution of per capita GDP, employment, household income distribution and the consumer price index, and looks at how income inequality and poverty have changed over the past two decades. It discusses changes that occurred in social stratification during the COVID-19 pandemic and addresses the worrying silent crisis of education as another of the pandemic’s major consequences including access to quality alternatives for continuing education and the availability of resources for remote learning. The publication delves upon access to education and the unequal labour impacts of the pandemic on men and women. It also analyses the social institutional framework and the evolution of social spending in Latin America and the Caribbean.